Rendimiento laboral de los funcionarios del Gobierno Autónomo Descentralizado Parroquial Caracol - Jimenez Marquez, Ernesto Estiven (2019)
The present research work was carried out at Government autonomous decentralized parish Caracol, was founded in the year of 1570, is located in the Buenaventura Burgos Street behind the central park of the snail parish, he is in charge of boost territorial development of the parish. This research aims to identify the problems that arise in the snail parish GAD, which disadvantage in any way in job performance and prevents development of capabilities are part of the public entity, be subsequently mentioned the shortcomings which makes it impossible to perform fluent respective works, which influence working efficiency expected by an institution in relation to their objectives or goals